1998
DOI: 10.1890/1051-0761(1998)008[0706:neinae]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Excess in North American Ecosystems: Predisposing Factors, Ecosystem Responses, and Management Strategies

Abstract: Most forests in North America remain nitrogen limited, although recent studies have identified forested areas that exhibit symptoms of N excess, analogous to overfertilization of arable land. Nitrogen excess in watersheds is detrimental because of disruptions in plant/soil nutrient relations, increased soil acidification and aluminum mobility, increased emissions of nitrogenous greenhouse gases from soil, reduced methane consumption in soil, decreased water quality, toxic effects on freshwater biota, and eutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(122 citation statements)
references
References 226 publications
2
115
0
Order By: Relevance
“…Experiments with labelled N elsewhere confirmed that added ammonium was especially retained within the organic layer and upper mineral soil where microbial activity was the highest (Gundersen 1998;Nadelhoffer et al 1999Nadelhoffer et al , 2004Feng et al 2008). The soil organic N pool was also identified as the major sink of deposited DIN in several other studies (Magill et al 1997;Fenn et al 1998;Rueth and Baron 2002). It is also likely that chemical exchange of NH 4 ?…”
Section: Features Of Inorganic Nitrogen Retention: Role Of N Form Andmentioning
confidence: 76%
See 1 more Smart Citation
“…Experiments with labelled N elsewhere confirmed that added ammonium was especially retained within the organic layer and upper mineral soil where microbial activity was the highest (Gundersen 1998;Nadelhoffer et al 1999Nadelhoffer et al , 2004Feng et al 2008). The soil organic N pool was also identified as the major sink of deposited DIN in several other studies (Magill et al 1997;Fenn et al 1998;Rueth and Baron 2002). It is also likely that chemical exchange of NH 4 ?…”
Section: Features Of Inorganic Nitrogen Retention: Role Of N Form Andmentioning
confidence: 76%
“…The low N uptake of the forest and the coarse textured soil (low hydrological residence times and low cation exchange capacity due to low clay content) might have predisposed the forest to low N retention and excessive NO 3 -losses (Fenn et al 1998). Also soil acidity could exacerbate N losses in different ways (Venterea et al 2004).…”
Section: Drivers Of Inorganic Nitrogen Leachingmentioning
confidence: 99%
“…Anthropogenic nitrogen (N) deposition now rivals natural N inputs, and this has had widespread effects on terrestrial and aquatic ecosystems (Vitousek et al 1997;Fenn et al 1998;Langham 1999). One of the most intensively-studied aspects is the effect of atmospheric N deposition on litter decay in forests (Berg and Laskowski 2005), as alterations in decomposition rates will effect forest carbon sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that soils under Abies pinsapo Wr forests would show less N retention capacity overall than reported in more mesic temperate forest ecosystems. Mediterranean ecosystems have a limited capacity to retain N inputs (Riggan et al 1985;Fenn et al 1996;Fenn and Poth 1999), principally due to high nitriWcation rates, short growing seasons, and temporal asynchrony between hydrological loss Xuxes and plant N demand, mainly as a consequence of summerdry periods followed by intense autumn rains (Fenn et al 1998;Meixner et al 2001). A second hypothesis is that rates of abiotic immobilization of soil NO 3 ¡ would be higher in the N limited stand than in the N saturated site.…”
Section: Introductionmentioning
confidence: 99%